2007
DOI: 10.1021/jp072929c
|View full text |Cite
|
Sign up to set email alerts
|

Solid−Solid Structural Transformations in Lennard-Jones Clusters:  Accurate Simulations versus the Harmonic Superposition Approximation

Abstract: We consider systems undergoing very-low-temperature solid-solid transitions associated with minima of similar energy but different symmetry, and separated by a high potential barrier. In such cases the well-known "broken-ergodicity" problem is often difficult to overcome, even using the most advanced Monte Carlo (MC) techniques, including the replica exchange method (REM). The methodology that we develop in this paper is suitable for the above specified cases and is numerically accurate and efficient. It is ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
79
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 36 publications
4
79
0
Order By: Relevance
“…For LJ 17 the efficiency gain of nested sampling is a factor of 10 over parallel tempering, while for the larger LJ 25 cluster, as the entropy jump is larger, the efficiency gain is a factor of 100. Our heat capacity curves for the largest clusters (LJ 31 , LJ 36 and LJ 38 ) are consistent with what is reported in the literature [38,42], using computational resources of similar order of magnitude. Note however, that advance knowledge of the global minimum is not required and was not used in the nested sampling simulations.…”
Section: Lennard-jones Clusterssupporting
confidence: 89%
“…For LJ 17 the efficiency gain of nested sampling is a factor of 10 over parallel tempering, while for the larger LJ 25 cluster, as the entropy jump is larger, the efficiency gain is a factor of 100. Our heat capacity curves for the largest clusters (LJ 31 , LJ 36 and LJ 38 ) are consistent with what is reported in the literature [38,42], using computational resources of similar order of magnitude. Note however, that advance knowledge of the global minimum is not required and was not used in the nested sampling simulations.…”
Section: Lennard-jones Clusterssupporting
confidence: 89%
“…In particular, it provides a framework to circumvent many difficulties associated with sampling problems arising from high potential energy barriers, which often lead to trapping, broken ergodicity, and rare event dynamics. The principal distinction between these methods and the huge variety of alternative approaches to enhanced sampling [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] and rare events [17][18][19][20] is the use of stationary points of the potential energy to provide an initial coarse-graining. Limits can be defined that permit either high accuracy or systematic approximations to be applied.…”
Section: Introductionmentioning
confidence: 99%
“…42 Solid-solid structural transitions are frequently found to precede melting for Lennard-Jones ͑LJ͒ clusters, resulting in two well-resolved peaks in heat capacity. [44][45][46][47][48][49][50] For example, using exchange Monte Carlo simulations Mandelshtam et al found that LJ n clusters with n = 74-78 have two peaks in their heat capacities. 46 The peak at higher temperatures is attributed to a melting transition, and the lower temperature peak is assigned to a solid-to-solid structural transition from the decahedral ground state to an icosahedral geometry.…”
Section: Introductionmentioning
confidence: 99%